2011
DOI: 10.1016/j.juro.2011.03.141
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Nonmuscle Invasive Bladder Cancer Recurrence Detection Using a Urine Based FGFR3 Mutation Assay

Abstract: Introduction. The assessment of risk of recurrence and progression of bladder cancer (BC) is still rather difficult. We decided to check the rates of the changes mentioned above in the group of the Polish patients after a year-long observation and next to compare them with the results calculated in the Euro-pean Organisation of Research and Treatment of Cancer (EORTC) risk tables. Methods. The tested group consisted of 91 patients who underwent transurethral resection of bladder tumour (TURBT). When being diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 23 publications
1
32
0
Order By: Relevance
“…This could probably be improved by analyzing more than one urine sample as we showed previously for the FGFR3 mutation assay (27). Another possibility would be to increase the analytical sensitivity of the assays.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This could probably be improved by analyzing more than one urine sample as we showed previously for the FGFR3 mutation assay (27). Another possibility would be to increase the analytical sensitivity of the assays.…”
Section: Discussionmentioning
confidence: 95%
“…Up to 80% of the pTa tumors have a mutation in the fibroblast growth factor receptor 3 (FGFR3) oncogene (25,26). We showed that a multiplex assay for the most common mutations was able to detect about 75% of tumors smaller than 1.5 cm and 100% if the tumors were larger than 3 cm (27). A great advantage of the FGFR3 assay is that as these mutations are extremely rare in normal cells, an assay to detect FGFR3 mutations has a specificity of 100%.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, previous studies evaluating the accuracy of detecting FGFR3 mutations in voided urine in the context of the follow-up of patients after TUR showed an estimated sensitivity in the range of 0.58 to 0.66 in patients with an FGFR3 mutation in the primary tumor (9,13,16,17,30), with an apparent specificity of about 0.95.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Mutations in fibroblast growth factor 3 (FGFR3) are found in a large proportion of non-muscle invasive bladder cancers (12) and may M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 2 therefore represent useful biomarkers for the follow-up of patients with B-TCC. Ten different FGFR3 mutations have been described in bladder cancer and 4 mutations (S249C, Y375C, G372C, and R248C) account for 95% of mutated FGFR3 (13). It has been shown that urine-based FGFR3 mutation analysis can detect recurrence, although its sensitivity may be limited if samples have few tumor cells (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation